Hyperferritinemia as a factor associated with poor prognosis in COVID-19 patients - Al-Dulaimi, Nuhad Mohammed; Mohammed, Mahmood Jassim; Mutlk, Saad T; Al-Rawi, Khalid F; Ali, Hameed Hussein; Aldahham, Bilal J M; Al-Ani, Faisal; Al-Ani, Osamah; Hamed, Yaqout A; Ali, Aus T (Ceska a Slovenska farmacie, 2023)
Worldwide, hundreds of millions of people have been infected with COVID-19 since December 2019; however, about 20% or less developed severe symptoms. The main aim of the current study was to assess the relationship between the severity of Covid-19 and different clinical and laboratory parameters. A total number of 466 Arabs have willingly joined this prospective cohort. Out of the total number, 297 subjects (63.7%) had negative COVID-19 tests, and thus, they were recruited as controls, while 169 subjects (36.3%) who tested positive for COVID-19 were enrolled as cases. Out of the total number of COVID-19 patients, 127 (75.15%) presented with mild symptoms, and 42 (24.85%) had severe symptoms. The age range for the participants was 20 to 82 years. Compared with controls, the severity of the disease was associated with significantly high ferritin levels (P < 0.001). The severity of the disease was also associated with a significant increase in C-reactive protein (P < 0.001), D-dimer (P < 0.001), white blood cell count (WBC) (P < 0.01), IgM (P < 0.001), and Granulocytes (P < 0.01). In addition, severe COVID-19 symptoms in the current study were associated with a significant decrease in lymphocytes (P < 0.01). There was a four-fold increase in serum ferritin levels in COVID-19 patients presented with severe symptoms upon admission. The former was associated with significantly high levels of CRP and D-dimer. Thus, hyperferritinemia, together with high CRP and D-dimer concentrations, may serve as reliable predictors for disease severity and poor prognosis in Arabs with COVID-19.
Keywords: senioři; Hyperferritinemia; senioři nad 80 let; Prognosis; Middle Aged; Ferritin; COVID-19; mild symptoms; Prospective Studies; Adult; mladý dospělý; hyperferritinemie; Aged, 80 and over; Young Adult; severe symptoms; prognóza; Humans; prospektivní studie; lidé středního věku; dospělí; poor prognosis; ferritiny; Aged; lidé; Ferritins